2013
DOI: 10.1155/2013/238943
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Dominance and Visual Function Testing

Abstract: Purpose. To show the distribution of ocular dominance as measured with sensory and eye sighting methods and its potential relationship with high and low contrast LogMAR visual acuity in presbyopic subjects. Method. Forty-four presbyopes (48.5 ± 3.5 years) participated in this study. Ocular dominance was determined by eye sighting (hole-in-card) and sensorial (+1.50 D lens induced blur) methods. According to the dominance detected with each method (RE: right eye or LE: left eye), patients were classified in dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 29 publications
(34 reference statements)
2
40
1
Order By: Relevance
“…7). This is consistent with a body of previous findings indicating the prevalence of RE sighting dominance (see summary table in Lopes-Ferreira, Neves, Queiros, Faria-Ribeiro, Peixoto-de-Matos & Gonzalez-Méijome, 2013). We also found that RE SED (61.2% of observers) was more prevalent than LE SED (38.8% of observers; see Figs.…”
Section: Resultssupporting
confidence: 93%
“…7). This is consistent with a body of previous findings indicating the prevalence of RE sighting dominance (see summary table in Lopes-Ferreira, Neves, Queiros, Faria-Ribeiro, Peixoto-de-Matos & Gonzalez-Méijome, 2013). We also found that RE SED (61.2% of observers) was more prevalent than LE SED (38.8% of observers; see Figs.…”
Section: Resultssupporting
confidence: 93%
“…We believe that the right eye significantly had a higher degree of myopia is related to ocular dominance. It is known that right eye dominance is more common than left eye dominance in human population [9]. In a study including 543 Singaporean children, Chia et al [10] reported that when the interocular difference in refractive power exceeded 1.50 D, the dominant eye was more myopic in 56 % of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory dominance was assessed on all participants using the alternate blur method 24 (single +1.50 D trial lens alternated in front of the participant's eyes with the eye reporting greatest subjective blur deemed the dominant eye), and if the dominant eye was identified, no more eye dominance testing was performed. If sensory eye dominance could not be identified, sighting eye dominance was determined using the sighting method 24 (“hole-in-the-hand technique”).…”
Section: Methodsmentioning
confidence: 99%